2015
DOI: 10.1002/jmri.24880
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in 3D time-resolved contrast-enhanced MR angiography

Abstract: Contrast-enhanced MR angiography (CE-MRA) was first introduced for clinical studies approximately 20 years ago. Early work provided 3 to 4 mm spatial resolution with acquisition times in the 30 sec range. Since that time there has been continuing effort to provide improved spatial resolution with reduced acquisition time, allowing high resolution three-dimensional (3D) time-resolved studies. The purpose of this work is to describe how this has been accomplished. Specific technical enablers have been: improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 137 publications
0
18
0
Order By: Relevance
“…28,29 On the other hand, TR-MRA enables visualization of the temporal dynamics of blood flow and captures a clear arterial phase with minimal venous contamination. 16,30,31 Commercial TR-MRA techniques such as TRICKS, time-resolved imaging with stochastic trajectories (TWIST; Siemens, Erlangen, Germany), or 4D TR-MRA with Keyhole (4D-TRAK; Philips Healthcare, Best, the Netherlands) should provide a similar level of image quality. 32 In this study, TRICKS was used.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 On the other hand, TR-MRA enables visualization of the temporal dynamics of blood flow and captures a clear arterial phase with minimal venous contamination. 16,30,31 Commercial TR-MRA techniques such as TRICKS, time-resolved imaging with stochastic trajectories (TWIST; Siemens, Erlangen, Germany), or 4D TR-MRA with Keyhole (4D-TRAK; Philips Healthcare, Best, the Netherlands) should provide a similar level of image quality. 32 In this study, TRICKS was used.…”
Section: Discussionmentioning
confidence: 99%
“…With the former technique, Lindenholz et al 10 in a larger cohort of 53 patients with SDAVF, demonstrated accurate localization of the level and side of fistula in 81% of the cases; however, the localization was incorrect or could not be predicted in 10 patients (19%). The latter MR method, also known as contrast-enhanced, time-resolved MRA, is a vendor-specific technique recently introduced to investigate vessel flow with the aim of achieving optimal temporal and spatial resolution 19 20. Two studies evaluating the usefulness of this technique have shown that the fistula was localized to one vertebral level in 82% and 85%; however, accurate localization was possible in only 70.2% and 50%, respectively 12 13.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple individual technical improvements contributing to this have been documented in the literature over this time period, and there have also been a number of review articles which have covered various aspects of this evolution. 3 , 4 This work, which is based on a presentation made at the September 2016 Japanese Society of Magnetic Resonance in Medicine, briefly reviews these major advances which have led to the current high level of performance. These include means for providing reliable timing and venous suppression, and multiple techniques such as view sharing and parallel acquisition for increasing the frame rate.…”
Section: Introductionmentioning
confidence: 99%